THE STUDY OF ENVIRONMENTAL PROTECTION IN SECONDARY SCHOOLS - Urazov, Abduxoliq; Eshtuxtarova, Orzigul; Taylanov, Nizom (Физико-технологического образование, 2021)
As we know that the problems of the environment are relevant at the same time. In addition, the impact of human society on the environment is significant. Only joint activity of people, carried out on the basis of a full understanding of the laws of nature, can save the planet. We must understand that it is a part of nature, and depends on the existence of other living beings. To understand the importance of human activity, environmental education should begin at preschool age